EDUCATION MANAGEMENT PERSPECTIVES PROPHET IBRAHIM - sulistiawati tia _; Danial Hilmi ((الطموحات ) EL-THUMUHAT, 2019)
It is important to emulate the education management perspectives prophet Ibrahim, where management of education has existed since the time of the prophets and the nature of management has existed and has grown naturally since the existence of this life. We first learned management from the time of the Prophet Adam to the time of the Prophet Muhammad. Here researchers focus more on the education management perspectives prophet Ibrahim. As mentioned in the Qur’an, it is emphatic that God established the Prophet Ibrahim with the nickname as "Father of the Prophets" which is a role model for Muslims to navigate life in this world. On the other hand prophetic management is a management model that is encouraged by the values ​​of the Qur'an and the values ​​exemplified by the Prophet directly. In fact, the elements of management have been described in the Qur'an through symbols such as the caliph, and also the hadith of the Prophet. One of them is the self-image of the Prophet Ibrahim through the nature of: honesty, trustworthy, truth, delivery of intelligence, compassion, patience, example, and democracy. So it should be from us to follow every step of his journey.